Individual performance progression of German elite female and male middle-distance runners. Issue 3 (4th March 2021) - Weippert, Matthias; Petelczyc, Monika; Thürkow, Christoph; Behrens, Martin; Bruhn, Sven
Abstract: Current standards for talent identification often base on age-related cross-sectional or mixed data analyses. Longitudinal studies of elite runners from their very early to their late career are still rare, despite their need for valid talent identification and prognoses. Thus, we analysed individual performance trajectories of German international level middle-distance runners (30 females, 41 males) from an age of 14 until their top performance. Quadratic equations best fitted the individual performances from 14 years to late career in relation to the world record time. The individual trajectories were further used to construct a global performance progression model, providing annual performance estimates (mean and standard deviation of 800, 1000 and 1500 m race times in relation to the current world record time) of later top runners from early to late career. Our analysis implies that, on average, females started from a higher performance level at young age. In contrast, average performance progression of the males was higher until the age of 17 years. Performance peaked at an age of 24.0 ± 3.0 and 23.3 ± 2.6 years for the female and male runners, respectively. The provided average annual performance progressions, as well as their ranges, may help coaches and sport federations in their decision making on age-related performance criteria for talent identification in middle-distance running.